2010
DOI: 10.1111/j.1440-1746.2009.06018.x
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of primary biliary cirrhosis and autoimmune hepatitis: Characteristics, therapy, and long term outcomes

Abstract: Background: Coexistence of primary biliary cirrhosis (PBC) and autoimmune hepatitis (AIH) is referred to as PBC-AIH overlap. Pathogenesis of PBC-AIH is not well understood and its diagnosis is challenging. We previously reported the clinical characteristics of 10 patients diagnosed with PBC-AIH overlap. Aims: The aim of the study was extend the earlier series and evaluate the diagnostic criteria, biological characteristics, potential therapy, and long-term outcomes of patients with PBC-AIH overlap. Methods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 33 publications
3
43
0
1
Order By: Relevance
“…10 For patients with overlap syndrome of AIH-PSC or AIH-PBC a combination therapy of immunosuppression with urso deoxy cholic acid (UDCA) is recommended. 1,11 AZA and 6MP are well tolerated in majority, with few adverse effects including nausea, vomiting, rash, arthralgia, fever, pancreatitis, hepatotoxicity and/or cytopenia which require dose modification or discontinuation. There is no established second line therapy for AIH patients who fail, i. e. intolerant or non-responsive to AZA therapy due to lack of randomized controlled trials.…”
mentioning
confidence: 99%
“…10 For patients with overlap syndrome of AIH-PSC or AIH-PBC a combination therapy of immunosuppression with urso deoxy cholic acid (UDCA) is recommended. 1,11 AZA and 6MP are well tolerated in majority, with few adverse effects including nausea, vomiting, rash, arthralgia, fever, pancreatitis, hepatotoxicity and/or cytopenia which require dose modification or discontinuation. There is no established second line therapy for AIH patients who fail, i. e. intolerant or non-responsive to AZA therapy due to lack of randomized controlled trials.…”
mentioning
confidence: 99%
“…AIH mouse models have also shown that CpG stimulation results in the breakdown of immune tolerance and induces transient AIH and that inflammation subsides upon the cessation of stimulation. TLR9 stimulation may also be involved in the onset of AIH 13,14) . In addition, hyperimmunoglobulinemia may have been caused by an excessive natural immune response via elevated TLR9 expression due to chronic bacterial stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with a steroid is often effective for PBC -AIH overlap 14,17) . The present case also responded to steroid treatment, resulting in evident improvement in hepatitis and a decrease in IgM level.…”
Section: Discussionmentioning
confidence: 99%
“…Az overlap gyakorisága nagyban függ az alkalmazott pontrendszertől. Az AIH/PBC overlap gyakorisága 4,8-19% PBC-s betegekben és 5-8,3% AIHbetegekben, Yokokawa és mtsai vizsglatában 11, illetve 12% volt [29], átlagosan 10% körül van [30].…”
Section: Aih/pbc Overlapunclassified